Electromagnetic Imaging of Two-Dimensional Geometries by Multipulse Interference Using the Inverse FDTD Method. (30th March 2014) - Okada, Naoki; Cole, James B.
Abstract : The size, shape, and location of unknown objects in the ground and in the body can be estimated by an electromagnetic imaging technique. An imaging approach to clear detection of two-dimensional geometries is proposed in this paper. Based on the inverse finite-difference time-domain (FDTD) method, a phase interference technique using multidirectional pulses is employed. The advantage of the proposed method is that it can clearly reconstruct the geometry in a simple calculation. Sample imaging results are demonstrated. The analysis of the FDTD results shows that the detectable object size is limited by the incident wavelength and the measurement spacing and illustrates the detectability of multiple objects.